S43 In-hospital mortality and length of stay following cardiovascular events and interventions in people with bronchiectasis: a population based study. (15th November 2017) - Plowright, M; Hutchinson, JP; Quint, JK; Hubbard, RB; Navaratnam, V
Abstract : Background: The incidence and prevalence of bronchiectasis is increasing. Epidemiological studies have reported that people with bronchiectasis are at increased risk of cardiovascular co-morbidities. However, there are limited data on outcomes after acute myocardial infarction (AMI), coronary artery bypass graft (CABG) or percutaneous angioplasty (PCI) amongst people with bronchiectasis. The aims of our study were to determine in-hospital mortality and mean length of hospital stay (LOHS) following AMI, CABG and PCI in people with and without bronchiectasis. Methods: We used data from the Nationwide Inpatient Sample, an anonymised stratified yearly sample of discharge records from community hospitals in the USA developed for the Healthcare Cost and Utilisation Project. People with a record of bronchiectasis from 2000 to 2011 were identified using the International Classification of Diseases (ICD-9-CM) codes. ICD-9-CM and procedure codes were also used to identify people with AMI, CABG and PCI. Multivariable logistic regression was used to estimate odds ratios for in-hospital mortality following AMI, CABG and PCI in people with and without bronchiectasis, adjusting for age and sex. We also compared mean LOHS following AMI, CABG and PCI between individuals with bronchiectasis and the general population. Results: We identified 1 01 597 people with a record of bronchiectasis. The mean age of the cohort was 57.2 years (Standard Deviation 20.8) and 60.8% were female. 2195 (2.2%) individuals with bronchiectasis had an AMI, 366 (0.4%) had undergone a CABG and 827 (0.8%) underwent a PCI. In-hospital mortality amongst people with bronchiectasis following AMI, CABG and PCI was 12.5%, 3.6% and 2.9% respectively. After adjusting for age and sex, we found no difference in in-hospital mortality following AMI, CABG or PCI in people with bronchiectasis compared to the general population (Table 1 ). Individuals with bronchiectasis had a longer mean LOHS following AMI, CABG and PCI (Table 1 ). Conclusions: Our findings suggest no difference in risk of death following AMI, CABG and PCI in people with bronchiectasis, which should be taken into account when counselling patients. However, individuals with bronchiectasis had a longer mean LOHS, which may impact healthcare resources and patient care pathways.